Process and outcome of a four-week garden-enhanced nutrition education programme to improve knowledge and vegetable consumption of school-age children in Ibadan, Nigeria - Shirley I. Ejoh; Ifeoluwa Bodunde; Aminat Oyedele; Melanie A. Gerdes; Rachel E Scherr (World Nutrition, 2025)
Background Diets of school-age children are increasingly becoming energy-dense, coupled with the poor consumption of vegetables and fruits. This situation predisposes them to malnutrition and non-communicable diseases. A garden-enhanced nutrition education programme was therefore designed to promote knowledge and consumption of vegetables. Objective To design a garden-enhanced nutrition education programme to promote knowledge and consumption of vegetables. Methods A 4-week garden-enhanced nutrition education pilot programme tagged ‘Kids Nutri garden Vacation School (KNGVS) was implemented during the long vacation of elementary schools. School-age children 6 – 11 (n=24) participated in the programme. The intervention included weekly outdoor and indoor activities of hands-on vegetable gardening, nutrition education lessons, and a cooking demonstration session. Data on nutrition knowledge, asking behaviour and consumption of vegetables were obtained at baseline (pre-test), endline (post-test) and six weeks follow-up and compared using one way ANOVA. Qualitative data on parents’ perception of the intervention programme was obtained and reported thematically. Results There was a statistically signifcant increase in nutrition knowledge scores: pre-test = 39.2±9.1, post-test = 48.3±6.7, which was maintained at the 6-week follow-up = 48.9±4.4, F=13.45, p<0.00). The number of children who reported that they ate vegetables always also increased: pre-test =12.5%, post-test = 20.8%, follow-up = 33.3%. All parents (100%) reported that their children had become more conscious of consuming vegetables and healthy food choices to a great extent. Conclusions The garden-enhanced nutrition education approach is a promising food-system related framework that provides a window of opportunity for influencing knowledge and practice of healthy eating among school-age children in developing countries like Nigeria. It leverages hands-on learning to give the children first-hand experience on the linkages between nutrition, health, agriculture and the environment at different levels of social interaction. There is a need to test this framework further while implementing it at a larger scale within the regular primary school academic calender.